Looking Back on the Lessons of "Higher Education and Developing Countries: Peril and Promise": Perspectives on China and India - David E. Bloom; Philip G. Altbach; Henry Rosovsky (Institute for the Study of Labor (IZA), 2016)
In 2000, Higher Education in Developing Countries: Peril and Promise was published. This report, cosponsored by The World Bank and UNESCO, came at a time of transition in higher education worldwide and helped shape higher education policy and thinking in several developing countries. This article looks at some of the main arguments in Peril and Promise. It focuses particularly on how two key countries, China and India, have developed in light of the key recommendations in Peril and Promise.
Keywords: I25; I28; I29; 330; higher education policy; developing countries; higher education; peril and promise; China; India